Um conversor Push-Pull Boost trabalhando com alto fator de potência empregando um filtro passivo sintonizado - Coelho, Frederico Augusto Bernardes (2006)
This work presents a complete study regarding the Push-Pull Boost topology associated with a notch filter, discoursing about improvements over other existing approaches, operating features, mathematical analysis, and design issues. Moreover, the notch filter is proposed and studied, since the application in the reduction of high frequency harmonics is emphasized. Experimental results confirm the ability to achieve high power factor, low total harmonic distortion, and high efficiency in a single power stage with low cost and reduced complexity.